Strategi Pengembangan Wisata Kolam Pemancingan Dusun Kedungrejo - Oktaviani, Annis; Puspita, Cindy Diah Ika; Amalia, Nurul Avina; Bataha, Katerina (Peneliti.net, 2023)
Tourism development is an effort made to complement and improve the services and facilities needed by tourists so they can feel comfortable while visiting tourist attractions. The existence of tourism development also not only provides benefits for tourists, but also for the surrounding community. The tourism development carried out will of course provide benefits for the local community both in terms of culture, economy, and social. This tourism development effort is in accordance with what was carried out by the Balonggebang Village Government, Gondang District, Nganjuk Regency, which utilizes fishing tourism as one of the potentials in the area. Unfortunately, the development of these tourist attractions is still experiencing obstacles due to the lack of an active role from the community and the human resources they have are also considered lacking. Therefore, it is hoped that with the contribution of people outside the area by helping to improve and develop fishing tourism spots, it will be able to maximize development. With the active role of both the local community and assistance from outside the area in developing the Kedungrejo Fishing Pond tourist spot, of course this will increase the popularity of this tourist spot, and will be able to generate profits.